Loculated Right-Sided Hydropneumothorax Mimicking Giant Pulmonary Bullae in a Post-Tuberculosis Patient: A Multimodality Imaging Diagnostic Challenge - Sidik Teghar Sanyadi; Bernard Sujijanto Suwito; Gandhi Estrada Atmanto (Phlox Institute: Indonesian Medical Research Organization, 2026)
Introduction: Post-tuberculosis lung disease remains a significant public health challenge affecting millions of individuals globally, representing a substantial health burden in tuberculosis-endemic regions and in developed countries with immigration from endemic areas. Loculated hydropneumothorax as a late complication of successfully treated pulmonary tuberculosis is a rare but diagnostically challenging entity, particularly when imaging findings suggest alternative pathology such as giant pulmonary bullae. This case illustrates the complexity of post-tuberculosis complications and the essential role of multimodality imaging. Case Presentation: A 63-year-old retired woman presented to the emergency department with three days of progressive dyspnea accompanied by productive cough with yellowish-white sputum. Physical examination revealed severe tachypnea (41 breaths per minute), clinically significant hypoxemia (SpO₂ 88 percent on room air), and diminished breath sounds over the right hemithorax with crackles in the right upper lobe. Chest radiography demonstrated a large thin-walled cavity (18 by 9.5 by 14 centimeters) with a horizontal air-fluid level in the right hemithorax, mediastinal leftward shift, and right costophrenic sinus obliteration. Thoracic point-of-care ultrasound revealed predominant gas throughout the right hemithorax with minimal pleural fluid in dependent zones and absence of identifiable lung tissue above the hemidiaphragm. Contrast-enhanced computed tomography definitively identified loculated right-sided hydropneumothorax with thin-walled pleural compartment, air-fluid level, compressive atelectasis of right lower and middle lobes, and post-tuberculosis fibrotic sequelae. Individual imaging modalities — radiography, ultrasound, and computed tomography — each contributed essential diagnostic information, demonstrating that none is sufficient in isolation. Conclusion: Loculated hydropneumothorax must be considered in the differential diagnosis of large cavitary lesions in post-tuberculosis patients. A multimodality imaging approach is essential for achieving diagnostic certainty and preventing unnecessary surgical intervention.